2004
DOI: 10.1002/eat.20059
|View full text |Cite
|
Sign up to set email alerts
|

Dissonance thin‐ideal and didactic healthy behavior eating disorder prevention programs: Results from a controlled trial

Abstract: Results provide evidence that both interventions effectively reduce risk factors for eating pathology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
81
0
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(94 citation statements)
references
References 38 publications
11
81
0
2
Order By: Relevance
“…In addition, the intervention led to significant improvements in body image for the women in the CDcombined group over time. These findings are consistent with other research that has used cognitive dissonance interventions (Matusek, Wendt, & Wiseman, 2004;Stice et al, 2006). For example, Stice et al (2006) randomly assigned 481 adolescent girls who had body image concerns to either a cognitive-dissonance, healthy weight, expressive writing control, or assessment-only control condition.…”
Section: Body Dissatisfactionsupporting
confidence: 85%
See 2 more Smart Citations
“…In addition, the intervention led to significant improvements in body image for the women in the CDcombined group over time. These findings are consistent with other research that has used cognitive dissonance interventions (Matusek, Wendt, & Wiseman, 2004;Stice et al, 2006). For example, Stice et al (2006) randomly assigned 481 adolescent girls who had body image concerns to either a cognitive-dissonance, healthy weight, expressive writing control, or assessment-only control condition.…”
Section: Body Dissatisfactionsupporting
confidence: 85%
“…Specifically, it was intended to determine if the female athletes who participated in the cognitive dissonance intervention versus those who underwent the healthy weight program or were in the non-intervention control group showed reductions in internalization of the thin ideal, body dissatisfaction, negative affect, bulimic symptoms, and dieting behaviors. Although previous research has shown that a cognitive-dissonance based intervention can reduce thin-ideal internalization, negative affect, dieting behaviors, body dissatisfaction, and eating disorder symptoms within the general female college student population (Matusek, Wendt, & Wiseman, 2004;Stice et al, 2003), such effects were not found among a specific subgroup of undergraduates, female student athletes. Due to the lack of findings, various recommendations were made to guide future intervention research within the at-risk female college population.…”
Section: A Dissonance-based Eating Disorder Preventionmentioning
confidence: 78%
See 1 more Smart Citation
“…CD has been studied by five independent labs (see for review of all studies; see also Green, Scott, Diyankova, Gasser, & Pederson, 2005;Matusek, Wendt, Wiseman, 2004;Mitchell, Mazzeo, Rausch, & Cooke;, and has been found to reduce the following ED risk factors: negative affect, internalization of the thin-ideal standard of female beauty, body dissatisfaction, maladaptive dietary restraint, and bulimic pathology . Two metaanalyses also found that ED prevention programs producing the largest effects were those that were interactive (not didactic), multi-session (not single session), and dissonance-based (not psychoeducational) (Stice & Shaw, 2004;Stice et al, 2007).…”
Section: Is One Of Very Few Ed Prevention Programs To Meet the Amementioning
confidence: 99%
“…Moreover, CDIs can also be effective as single session interventions further improving dissemination (Matusek, Wendt & Wiseman, 2004). Matusek and colleagues found a single session 1-hour CDI successfully reduced thin ideal internalization, drive for thinness and disordered eating among university woman at 4-week follow up.…”
mentioning
confidence: 99%